Italy : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2009)
Italy's 2008 Article IV Consultation describes the country's economic developments and policies. Output has been projected to contract by about 1\2 percent in 2008 and 1 percent in 2009, with risks tilted to the downside, linked to a further slowing of global growth and falling consumer confidence. The economy's ability to rebound quickly is hampered by rigidities in the product and labor markets, a lack of domestic competition, a likely slower pace of industrial restructuring, and weakness of the public finances.